Anatomical and Histological Structure of Reproductive Organs in Male Flying Squirrel Hylopetes Lepidus (Horsfield, 1822) - Nirvana, Shanghnesy Jovita; Luthfi, Muhammad Ja’far; Ekasari, Erna; Maghfiroh, Lailatul (Proceeding International Conference on Science and Engineering, 2019)
Flying squirrel (Hylopetes lepidus) is an Eutherial mamal (placental mammal), belong to the order Rodentia and belong to the family Sciuridae. Hylopetes lepidus had gray cheek as its unique characteristics. The reproductive organs are the key to success in maintaining the new descendants. Male reproductive organs will produce the male sex cells or spermatozoa. The purpose of the research is to examine the anatomical structure, morphometry, histomorphometry, and histological structure of male reproductive organs (penis, testicle, vas deferens, bulbouretralis gland, prostate and seminal vesicles) of Hylopetes lepidus. The method used in examining histological characteristics is Hematoxyin–Eosin staining method. The histological structure of reproductive organs were observed using optilab microscope. The results of the study showed that the adult male flying squirrel weighed 104.28 ± 0.64 gram. Anatomically, it has oval white reddist testicle. The testicle is located side out of the body cavity in the scrotum. Morphometric observation testicular showed that the right testes has volume 0.35 ± 0.07 ml, and the left has volume 0.35 ± 0.07 ml, weight of the right testicular 0.19 ± 0.01 gram, weight of the left testicular 0.18 ± 0.01 gram, diameter of the right testicular 6.35 ± 0.21 mm, diameter of the left testicular 6.35 0.21 mm, short diameter of the right testicular 3.45 ± 0.21 mm, and short diameter of the left testicular 3.45 ± 0.21 mm. The diameter of tubulus seminiferus 261,4 ± 0.14 ?m. The conclusion of this study compared to rodentia other testicular Hylopetes lepidus has a unique testicular bound by the connective tissue in the scrotum so that testicular included in class permanent descending testicular. The rhombus of the prostate gland are blunt, while histologically the sertoli cells in the seminiferus tubule shaped elongated, while in morphometry penis Hylopetes lepidus relatively longer than Mus musculus.